Locutionary, Illocutionary, and Perlocutionary Acts in Henry Johnson Movie (2025): A Speech Act Analysis - Nova Dyah Pitaloka; Sulistiani Sulistiani; Dini Arsya Kamila; Amanda Ravinska; Farrel Adhiyatmika (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study examines the types of speech acts in Henry Johnson's film (2025) using Austin's (1962) framework of locutionary, illocutionary, and perlocutionary acts and Searle's (1969) classification of speech acts. This study employs a qualitative descriptive methodology to collect and analyze the film's dialogue, elucidating the pragmatic functions inherent in the characters' speech acts. The analysis stated that speech acts function as important tools in the process of negotiation, emotion management, trust building, and interpersonal dynamics between characters. In general, this study emphasized that the film Henry Johnson (2025) practices natural communication and demonstrates the power of language in establishing social relationships, creating psychological impressions, and directing systematic interactions. This study also shown how the specific medium of film can serve as a rich venue for representation to deepen understanding of pragmatic phenomena in socialization. Thus, the results of this study are expected to add insight into the role of speech acts in constructing meaning, conflict, and resolution in cinematographic works.